Weeds reported in rice in south and southeast Asia - Moody, Keith (International rice research institute, 1989)
This book offers a comprehensive list of weeds reported to occur in rice in 15 countries of South and Southeast Asia. This is a reference to weed species in rice in South and Southeast Asia. .